2022
DOI: 10.1093/ntr/ntac278
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for E-cigarette Use, Vaping Patterns, and Cessation Behaviors Among US Adolescents

Abstract: Introduction This study sought to examine reasons for youth e-cigarette use in association with vaping patterns and cessation behaviors. Methods A national representative sample of current (past 30-day) e-cigarette users in grades 6-12 was analyzed using the National Youth Tobacco Survey, conducted from January to March 2020. An exploratory oblique factor analysis using a rotated pattern matrix to select salient variable-fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Therefore, when their favorite flavors are integrated back into tobacco flavors, it is expected that they would prefer the mixed flavor. Since the availability of flavors was among the top reasons for vaping and its initiation, especially in adolescents and young adults, the addition of these flavors in tobacco flavors would likely resuscitate the motivation for vapers to continue to vape [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when their favorite flavors are integrated back into tobacco flavors, it is expected that they would prefer the mixed flavor. Since the availability of flavors was among the top reasons for vaping and its initiation, especially in adolescents and young adults, the addition of these flavors in tobacco flavors would likely resuscitate the motivation for vapers to continue to vape [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the availability of flavors was among the top reasons for vaping and its initiation, especially in adolescents and young adults, the addition of these flavors in tobacco flavors would inevitably resuscitate the motivation for vapers to continue to vape. [35,36] Through applying generalized estimating equation (GEE) models on over 3,000 Reddit posts that co-mention e-cigarette use and health symptoms in the same Reddit posts from January 2013 to April 2019, it was found that tobacco flavor was more likely to be co-mentioned with respiratory and throat symptoms than other symptoms. [37] A specific examination of the JUUL pod tobacco flavor with health symptoms showed a high probability of co-mention of the JUUL tobacco flavor with the throat, respiratory, and cardiovascular symptoms using similar GEE models and Reddit posts from September 2016 to April 2019.…”
Section: Public Perceptions and Discussion Of Tobacco-flavored E-ciga...mentioning
confidence: 99%
“…Since the availability of flavors was among the top reasons for vaping and its initiation, especially in adolescents and young adults, it is likely that the addition of these flavors in tobacco flavors would resuscitate the motivation for vapers to continue to vape. 34,35 Through applying generalized estimating equation (GEE) models on over 3,000 Reddit posts that co-mention e-cigarette use and health symptoms in the same Reddit posts from January 2013 to April 2019, it was found that tobacco flavor was more likely to be co-mentioned with respiratory and throat symptoms than other symptoms. 36 A specific examination of the JUUL pod tobacco flavor with health symptoms showed a high probability of co-mention of the JUUL tobacco flavor with the throat, respiratory, and cardiovascular symptoms using similar GEE models and Reddit posts from September 2016 to April 2019.…”
Section: Public Perceptions and Discussion Of Tobacco-flavored E-ciga...mentioning
confidence: 99%